Chronic Morel-Lavallée Lesion in a Pediatric Patient: An Underrecognized Sequela after Trauma - Anthony O. Kamson; Bradley Lazzari; Joshua Murphy (Case Reports in Pediatrics)
Morel-Lavallée lesions are serious internal degloving injuries associated with trauma. Its diagnosis and treatment can be challenging. We describe the surgical treatment of a case of a chronic Morel-Lavallée lesion in a pediatric patient who sustained an injury to her left thigh during an all-terrain vehicle accident more than a year ago.